Paving the Way for Using Li2S Batteries. Issue 9 (8th July 2014) - Xu, Rui; Zhang, Xiaofeng; Yu, Cun; Ren, Yang; Li, James C. M.; Belharouak, Ilias
Abstract In this work, a novel lithium–sulfur battery was developed comprising Li2S as the cathode, lithium metal as the anode and polysulfide‐based solution as the electrolyte. The electrochemical performances of these Li2S‐based cells strongly depended upon the nature of the electrolytes. In the presence of the conventional electrolyte that consisted of lithium bis(trifluoromethanesulfonyl)‐imide (LiTFSI) salt dissolved in a solvent combination of dimethoxyethane (DME)/1, 3‐dioxolane (DOL), the Li/Li2S cells showed sluggish kinetics, which translated into poor cycling and capacity retention. However, when using small amounts of polysulfides in the electrolyte along with a shuttle inhibitor the Li2S cathode was efficiently activated in the cell with the generation of over 1000 mAh g−1 capacity and good cycle life.